English Language Needs Analysis of Industrial Engineering Students at the Institute of Technology and Business Riau Pesisir - Julanos Julanos; Welly Desriyati; Hanifatul Rahmi; Azhari Siregar; Fariz Kharisma (Journal of English Language and Education, 2026)
English language skills play a vital role in supporting students’ academic and professional development, particularly in Industrial Engineering. Therefore, a needs analysis is essential to identify the specific language competencies required in industrial contexts. This study employed a qualitative descriptive design to examine students’ English language needs, focusing on four main skills—writing, reading, speaking, and listening—as well as relevant language components. Data were collected through questionnaires distributed to 242 randomly selected from a population of 619 active Industrial Engineering students at the Institute of Technology and Business Riau Pesisir. The findings indicate that reading and writing skills in Occupational Health and Safety (OHS) and environmental contexts considered as primary subject, and office administration, technical production, and logistics are the secondary important subject. Meanwhile, speaking and listening skills are in office and OHS contexts considered as primary subjects, while production and logistics as secondary. Overall, students emphasize mastering language components to support workplace communication.